Risk and the Extent of Insurance - Genicot, Garance; Ligon, Ethan (World Bank, Washington, DC, 2013)
This paper proposes measures of income risk that households face, and of the extent of insurance effectively delivered by the various coping mechanisms those households use to minimize the consequence of that risk by (1) contrasting the expected utility of consumption an individual has with the utility that she would have from consuming her income in each period, adjusted to account for the price of these coping mechanisms; (2) detailing the steps necessary to apply these measures to panel data of household income and consumption; and (3) measuring income risk, consumption risk, and insurance using the Indonesia Family Life Survey (IFLS). Expected consumption represents on average 65 percent of the expected income for the IFLS households, suggesting households remain willing to forgo a non-negligible amount of consumption in order to smooth it. Comparing risk and insurance across households highlights geography and education as key determinants of the cost of risk for households.